PENGEMBANGAN METODE ZONASI DAERAH BAHAYA LETUSAN GUNUNG API STUDI KASUS GUNUNG MERAPI - Wikanti Asriningrum; Heru Noviar; - suwarsono (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2004)
Merapi volcano which has height 2.986 m is located at central of Java Island. This volcano is one of 129 active volcano in Indonesia. Considering the amount of volcano, we need a method as a mitigation system of eruption hazard. MOS-MESSR (1991) dan Landsat-ETM (2002) sata and supported by secondary data are used to identify and classify landform, drainage pattern, and land cover. The result are 10 classes of landform, 3 leruption hazard level of drainage pattern, and 9 classes of landform. Based on gemorphogical analysis during 11 years show that forest area decrease 13.062 Ha and hazard risk pattern increasa.